First steps towards the Lithuanian word association database - Vilkaitė-Lozdienė, Laura (Taikomoji kalbotyra, 2019)
This paper introduces the first version of the Lithuanian database of free association norms. This is an attempt to provide an open-access resource, which would be helpful for psycholinguists, linguists, computational linguists, and students. This version of the database includes 277 cue word forms. The responses were collected from 304 participants. In total 15,612 association pairs were recorded. The paper presents the procedure of collecting free associations and additional data available for researchers. It also provides a list of all cue words with their five most frequent associates and some summary statistics.
Keywords: free associations; exical associations; Lithuanian association database; Lithuanian association norms; association norms